Significance of Impurity Analysis in Antiviral Drug: A Critical Review - Ramakrishnan, Balaji; Raju, Jeyaprakash Mari; Thangavelu, Prabha; Mariappan, Esakkimuthukumar; Natarajan, Jawahar; Selvaraj, Jubie (Current Drug Research Reviews, 2025)
Today's pharmaceutical products are seeing a massive increase in impurity profiling. A drug substance or product will inevitably contain contaminants in trace amounts. According to pharmaceutical chemistry, impurities are undesirable substances found in pharmaceutical compounds with therapeutic activity. Due to their extraordinary potency and likelihood of toxicity, they may exhibit unanticipated pharmacological effects that are detrimental to human health. For the pharmaceutical sector, impurity management is currently a major concern. The impurity can appear in medicines either during the formulation process or after the produced Active Pharmaceutical Ingredients (APIs) have aged. The term “impurity profiling” refers to a collection of analytical procedures that include characterizing, quantifying, and describing the known and unknown impurities found in novel pharmacological compounds. Highly sophisticated analytical techniques and instrumentation are essential for identifying small elements (drugs, contaminants, breakdown products, and metabolites) in diverse matrices. Current references and articles reveal different impurities found in the APIs of antiviral drugs, techniques for locating them, and potential countermeasures for the interferences they produce in pharmaceutical analysis. Antiviral medications are a class of medications used to treat viral infections. They work by preventing the growth of the pathogen they are intended to treat. Drugs that target viral activities must enter host cells because viruses are obligatory intracellular entities and prevent the production of viral DNA, which is subsequently converted to triphosphate. Regulatory authorities now need not just purity profiles but also impurity profiles. This review also covers the origins of impurities, how they are classified, and the different analytical techniques used to identify and quantify them. It also covers the simple, rapid, accurate, precise, and exact creation of innovative analytical techniques for determining impurity levels.
Keywords: anti-viral drugs